An Assay Combining Droplet Digital PCR With Propidium Monoazide Treatment for the Accurate Detection of Live Cells of Vibrio vulnificus in Plasma Samples - Hu, Ling; Fu, Yidong; Zhang, Shun; Pan, Zhilei; Xia, Jiang; Zhu, Peng; Guo, Jing (Frontiers in Microbiology, 2022)
Vibrio vulnificus (V. vulnificus) is one of the most common pathogenic Vibrio for human, so the establishment of timely and credible detection methods has become an urgent needing for V. vulnificus illness surveillance. In this study, an assay combining droplet digital PCR (ddPCR) with propidium monoazide (PMA) treatment was developed for detecting V. vulnificus. The primers/probe targeting the V. vulnificus hemolysin A gene (vvhA), amplification procedures, and PMA processing conditions involved in the assay were optimized. Then, we analyzed the specificity, sensitivity, and ability to detect live cell DNA, while testing the performance of PMA-ddPCR in clinical samples. The optimal concentrations of primers and probe were 1.0 μM and 0.3 μM, respectively. The annealing temperature achieving the highest accuracy in ddPCR assay was 60 °C. With an initial V. vulnificus cell concentration of 108 CFU/mL (colony-forming unit per milliliter), the optimal strategy to distinguish live cells from dead cells was to treat samples with 100 μM PMA for 15 min in the dark, and expose them to LED light with output wavelength of 465 nm for 10 min. 23 strains were tested for the specificity of PMA-ddPCR assay. Only the V. vulnificus reference strain and 6 clinical isolates were observed positive signals. The limit of detection (LOD) and the limit of quantitation (LOQ) in pure culture solutions of V. vulnificus were 29.33 CFU/mL and 53.64 CFU/mL, respectively. For artificially clinical sample tests, V. vulnificus could be detected at the concentrations as low as 65.20 CFU/mL. The sensitive of the PMA-ddPCR assay was 15-40 folds more sensitive than the PMA-qPCR in this study. The PMA-ddPCR assay we developed provides a new idea to accurately detect live cells of V. vulnificus in clinical samples, which is of great significance to enhance public health safety and security capability and improve the emergency response level for V. vulnificus infection.